The Importance of Rapid Influenza Testing in Pediatric Primary Care: Experience During Three Consecutive Influenza Seasons (2016-2019) in Barcelona (Catalonia, Spain) - Diego van Esso; Monica Vilà; Cristina Andrés; Sheila Iglesias; Josep Ferrer; Lucia Losada; Gemma Ricos; Lorena Sanchez; Patricia Morera; Mar Pérez; Mª Angeles Ferrandez; Esther Hernando; et al. (Frontiers Media S.A., 2020)
Clinical diagnosis of influenza has low sensitivity in infants and children. Signs and symptoms are non-specific and similar to those of other respiratory viruses. Rapid influenza diagnostic tests (RIDTs) with adequate sensitivity and specificity used at the point of care can be useful for an etiologic diagnosis of influenza in primary care. This should have an impact on better management of these patients. We conducted a study during three consecutive influenza seasons (2016-2017, 2017-2018, and 2018-2019) in pediatric primary care settings collecting data from influenza point-of-care tests (POCTs)-confirmed ≤ 6-year-old patients. During the first two influenza seasons, antibiotic prescriptions and additional visits from influenza POCT-confirmed patients (Group_1) were compared to patients with influenza-like illness (ILI) (Group_2), or fever (2016 ICD-10 code R50) with no other signs of influenza (Group_3). Group_1 had 0.19 (2016-2017) and 0.23 (2017-2018) additional visits compared to 0.48 (2016-2017) and 0.49 (2017-2018) Group_2 p < 0.001 and 1.01 (2016-2017) and 0.80 (2017-2018) Group_3 p < 0.001. Antibiotic prescription was lower in Group_1 (10.2%) vs. Group_3 (17.2%) p < 0.002, difference statistically significant only for the 2017-2018 season. During the third season (2018-2019), RIDTs results were transmitted in real time to the reference laboratory ia the cloud, which strengthens the monitoring of circulating influenza viruses in the community. In our experience, the use of POCTs has a great potential in primary care specially in infants and young children in which the diagnosis maybe missed due to non-specific signs and symptoms.